Prevalence and risk factors for non-alcoholic fatty liver in children and youth with obesity - Carolina Jimenez-Rivera; Stasia Hadjiyannakis; Jorge Davila; Julie Hurteau; Mary Aglipay; Nick Barrowman; Kristi B. Adamo (BMC, 2017)
Abstract Background Non- Alcoholic Fatty Liver (NAFL) is a spectrum of liver diseases (LD) that ranges from benign fatty infiltration of the liver to cirrhosis and hepatic failure. Hepatic ultrasound (US) and serum alanine aminotransferase (ALT) are often used as markers of NAFL. Our aim is to describe prevalence of NAFL and associated findings on ultrasound (US) and biochemical parameters in a population of children and adolescents with obesity at the Children's Hospital of Eastern Ontario. Methods Children with Obesity (BMI >95th percentile) ages 8-17 years presenting to the Endocrinology and Gastroenterology clinics, without underlying LD were prospectively recruited from 2009 to 2012. Fasting lipid profile, HOMA IR) and serum adiponectin levels were measured. NAFL was defined as ALT > 25 and >22 IU/mL (males and females respectively) and/or evidence of fatty infiltration by US. Logistic regression was performed to assess associations. Results 97 children with obesity included in the study (Male 43%). Mean age was 12.9 ± 3.2 years (84% were older than 10 y). Mean BMI-Z score was 3.8 ± 1.4. NAFL was identified in 85%(82/97) of participants. ALT was elevated in 61% of patients. Median triglyceride (TG) level was higher in children with NAFL(1.5 ± 0.9 vs. 1.1 ± 0.5 mmol/L, p = 0.01). Total cholesterol, HDL, LDL and Non HDL cholesterol were similar in both groups(p = 0.63, p = 0.98, p = 0.72 and p = 0.37 respectively). HOMA IR was ≥3.16 in 53% of children(55% in those with NAFL and 40% in those without NAFL). Median serum adiponectin was 11.2 μg/ml(IQR 7.3-18.3) in children with NAFL vs. 16.1 μg/ml(IQR 9.0-21.9) in those without NAFL(p = 0.23). Liver US was reported as normal in 30%, mild fatty infiltration in 38%, moderate in 20% and severe in 12%. TG were significantly higher(1.5 mmol/L vs. 1.0 mmol/L, p < 0.01) and HDL-C was lower(1.0 mmol/L vs. 1.1 mmol/L, p = 0.05) in children with moderate and severe NAFL by US. BMI-Z score, HOMA IR, serum adiponectin and HDL levels were not associated with NAFL, however TG were significantly associated(OR = 3.22 (95% CI: 1.01-10.25, p = 0.04)). Conclusion NAFL is highly prevalent in obese children and youth. Elevated TG levels are associated with NAFL; these findings may serve as a noninvasive screening tool to help clinicians identify children with obesity needing liver biopsy and/or more aggressive therapeutic interventions.